Kepercayaan Kepada Debata Tiga Batu Tungku Sebagai Pola Kepercayaan Untuk Lebih Memahami Ajaran Allah Tritunggal Yang Kontekstual Di Mamasa - Abialtar Abialtar (Institut Agama Kristen Negeri Toraja, 2021)
The author understands that the Debata Tiga Batu Tungku belief system in the To Salu tribe in Mamasa can be an interesting instrument (which the authors call